2010
DOI: 10.1109/jstsp.2009.2038983
|View full text |Cite
|
Sign up to set email alerts
|

Time Reversal in Multiple-Input Multiple-Output Radar

Abstract: Abstract-Time reversal explores the rich scattering in a multipath environment to achieve high target detectability. Multiple-input multiple-output (MIMO) radar is an emerging active sensing technology that uses diverse waveforms transmitted from widely spaced antennas to achieve increased target sensitivity when compared to standard phased arrays. In this paper, we combine MIMO radar with time reversal to automatically match waveforms to a scattering channel and further improve the performance of radar detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 32 publications
2
60
0
Order By: Relevance
“…The channel is probed with f (e jω ) and the clutter backscatters rc(e jω ) are recorded. In modeling Hc(e jω ), we follow the approach presented in [4,5], where the clutter is characterized in the spatial and spectral domains, and represented as a multivariate complex Gaussian random process. The covariance matrix of the clutter returns Rr c is estimated in this step.…”
Section: Conventional Clutter Probingmentioning
confidence: 99%
See 2 more Smart Citations
“…The channel is probed with f (e jω ) and the clutter backscatters rc(e jω ) are recorded. In modeling Hc(e jω ), we follow the approach presented in [4,5], where the clutter is characterized in the spatial and spectral domains, and represented as a multivariate complex Gaussian random process. The covariance matrix of the clutter returns Rr c is estimated in this step.…”
Section: Conventional Clutter Probingmentioning
confidence: 99%
“…For the probing waveforms, we follow [4] and use the phase coding scheme Fi(e jωq ) = e j2πiq/Q F (e jωq ), for (1 ≤ i ≤ 10) and (0 ≤ q ≤ Q − 1) with Q = 10 bins, where F (e jωq ) is the DTFT of the linear frequency modulated signal…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fishler et al focused on the application of the target spatial diversity to improve detection performance and demonstrated that statistical MIMO radar provided great improvements over other types of array radars [14]. For low-grazing angle detection of MIMO radar, the authors in [15] utilized the time reversal technique in a multipath environment to achieve high target detectability. It was demonstrated that the improved target detectability can be obtained, compared with the commonly used statistical MIMO strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Featuring of its adaptive focusing characteristic, TR technique has been used in lots of applications such as underwater acoustics communication, medical, electromagnetic imaging, and ultra-wideband wireless communication [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Recently, one completely new approach to achieve super-resolution has been offered by TR technique [20][21][22].…”
Section: Introductionmentioning
confidence: 99%